(untitled) (Journal of Parents and Teachers, 2014)
Reality TV has ended up installing the maximum distrust in the media’s viewers about what is true and what is not. In addition, reality shows can negatively affect children and teenagers. This article presents several guidelines for discussing honesty in reality shows in the classroom with activities such as comparing it to movies.